Measuring effectiveness of foundation training program provided by Bangladesh Bank training academy - Rifat-Bin-Rahman, Md. (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.